Analisis Lingkungan Pengembangan Agribisnis Komoditas Unggulan Buah-Buahan Kabupaten Minahasa Utara Provinsi Sulawesi Utara - Mira Yulianti (AGRIDES: Jurnal Agribisnis Perdesaan, 2011)
Minahasa Utara has been known as center fruits producer in Sulawesi Utara Province for years. However, some problems is still faced by businessmen in order to develop these commodities, those are: high fluctuated prices, long gestation period, and land decrease. Therefore, environment analysis to develop fruits agribusiness that to be local advantages and have high competitiveness is needed. Exploratory method was used in this study. Primary data were gathered through questionnaires and interviews. Samples were taken purposively consist of: 5 government officers from Agricultural Agency and BP4K of Minahasa Utara, 3 villages chiefs, and 3 agribusinessmen. Analysis used was environment analysis of internal (IFE) and external factors (EFE). The results showed, the internal factors, which to be the strengths were: land resource, strategic location, local government policies, and existence of traders and seed breeders. On contrary, the weakness factors were: low technological use in post-harvest and product processing, fruits business management, institutional (farmer groups), and capital access. While, the external factors those to be opportunity were: promotion program in national and international events, increase in fruits demand, decentralization, horticulture development policies from Ministry of Agriculture. Nonetheless, the treats factors were: fluctuated fruits’ prices, coordination among government agencies, trade liberalization and globalization, and quality standards system. This study also suggested that: processing industry should be developed as well as fruits production and quality. Moreover, the human resources quality should be increased in terms of management, experiences and technological mastery.